FAKTOR-FAKTOR YANG MEMPENGARUHI RASIO SOLVABILITAS, LIKUIDITAS, RASIO AKTIVITAS, DAN FIRM SIZE TERHADAP PROFITABILITAS PADA PERUSAHAAN SAHAM SYARIAH SUB SEKTOR ADVERTISING, PRINTING, DAN MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2021: JURNAL PARADIGMA EKONOMIKA - Sudharyati, Neneng; Agustin Nengsih, Titin; Anggraini, Dessy; Efrina, Leni; Isnawati; Selviana; Sinta; Ismail, M. (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This research and analysis aims to obtain an empirical evidence regarding the effect of leverage, liquidity, total asset turnover, and firm size on profitability. This study uses secondary data that is quantitative. The technique used in this study is a sampling technique, the sampling technique used is purposive sampling, and the analytical method used is panel data regression analysis using the R Studio application. The research sample used in this study is 9 sharia stock companies in the advertising printing media sub sector listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period. The studyâ€™s results by testing the Â hypothesis using the t statistical test showed that the Solvency Ratio significantly positively Â affected profitability. In contrast, liquidity, activity ratio (total asset turnover) and firm size (Firm Size) had no significant effect on profitability.